Iniciativas de innovación social para redistribución de los trabajos de cuidado en los hogares para mujeres rurales - Luisa Fernanda Malaver-Fonseca; Lizeth Fernanda Serrano-Cárdenas; Hugo Fernando Castro-Silva (Mundo Fesc)
Various feminist movements have sought to make visible the care work that women perform daily in the home. This work has not been recognized by either the state or the current economic model, ignoring the contribution that women make to families, the state, and society through their work. With the arrival of COVID-19, women's situation has worsened considerably, not only economically and socially, but also has widened inequality gaps compared to men, creating a difficult situation for both women and their families. Considering this problem, this article seeks to answer the following research question: What social innovation initiatives could contribute to the redistribution of care work in the home for rural women in the department of Boyacá in the context of the post-COVID-19 pandemic? To answer this question, two objectives were posed: first, to contrast the factors that explain the inequitable distribution of unpaid household work identified in the literature with the life stories of rural women in the department of Boyacá, studying the implications of the COVID-19 pandemic on this dynamic. Second, to establish social innovation initiatives for the post-COVID-19 pandemic context, aligned with the factors that explain the inequity in the redistribution of unpaid household work based on the Human-Centered Design methodology. A methodological structure based on Human-Centered Design was established, comprising three phases: Listen, Create, and Deliver. The research results are expected to translate into social innovation initiatives that contribute to reducing and redistributing unpaid care work in rural households.